2007
DOI: 10.2495/rm070351
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional flow in a barb field

Abstract: Barbs (or submerged groynes) are low-profile linear rock structures that are primarily used to prevent the erosion of stream banks. They are a variation of a groyne, similar to spur dikes and bendway weirs. Barbs are typically anchored, in series, to the outside bank in stream bends and extend in an upstream direction from the bank into the flow. This configuration redirects flow away from the outer stream bank and disrupts the velocity gradient close to the outer bank, encouraging sediment deposition adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…However, the >5 m elevation change at the wing dike tip at site B that occurred between 29 May and 4 June (where vortex cores and z ‐vorticity are most pronounced on both days) suggests that (1) there could be a correspondence between vorticity and scour; and (2) that, in this case, the required flow may be just below the flood stage (4700 m 3 s −1 ), given the peak in the hydrograph between these dates (Figure 2) and subsequent changes to the scour hole shape and depth. Indeed, the most active region of bed mobility, the upstream scour hole crest (Figures 8 and 13), corresponds with the most concentrated contours of high positive z ‐vorticity (i.e., 4 June in Figure 14), supporting previous numerical results that indicate a correspondence between vorticity and local scour at submerged groyne tips [ Minor et al , 2007].…”
Section: Discussionsupporting
confidence: 85%
“…However, the >5 m elevation change at the wing dike tip at site B that occurred between 29 May and 4 June (where vortex cores and z ‐vorticity are most pronounced on both days) suggests that (1) there could be a correspondence between vorticity and scour; and (2) that, in this case, the required flow may be just below the flood stage (4700 m 3 s −1 ), given the peak in the hydrograph between these dates (Figure 2) and subsequent changes to the scour hole shape and depth. Indeed, the most active region of bed mobility, the upstream scour hole crest (Figures 8 and 13), corresponds with the most concentrated contours of high positive z ‐vorticity (i.e., 4 June in Figure 14), supporting previous numerical results that indicate a correspondence between vorticity and local scour at submerged groyne tips [ Minor et al , 2007].…”
Section: Discussionsupporting
confidence: 85%
“…As obstructions, ELJs are expected to produce vortices along the upstream face and downstream of the structure (Koken & Constantinescu, 2014). In addition, ELJs may produce flow structures similar to those created by groynes when they are emergent at low discharge (e.g., Paik et al, 2010) and flow structures similar to bendway weirs when they are submerged at high discharge (e.g., Minor et al, 2007). Even with these simplified shapes, studies have shown that more abrupt geometry changes produce stronger and more CFSs (Koken & Constantinescu, 2014).…”
mentioning
confidence: 99%